О систематическом положении комара-лимонииды Chionea crassipes Boh. (Diptera, Limoniidae) в пределах рода - Савченко, E.H. (Вестник зоологии, 1981)
The male hypopygium structure of Chionea crassipes В о h., in spite of 6-7 joint antennae, give reasons to relate it to the Ch. araneoides D a l m. group (the genus Chionea s. str., E n d e r l e і n, 1936) and not to the Ch. lutescens L u n d s t r. group (the genus Niphadobata Enderlein, 1936) where it is attributed to by Burghel-Balacesco (1969). Out of other palearctic species of the genus Chionea s. lato the Far-East Ch. gracilistyla A l e x a n d e r (1936) also belongs to the Ch. araneoides group.